Assessment of vitamin C supplementation as an adjuvant analgesic therapy and evaluating its efficacy in terms of clinical and functional outcomes in post-operative patients undergoing surgical decompression for prolapsed intervertebral lumbar disc - Garg, Rohit N.; Patil, Hrishikesh; Bajaj, Sanket; Vaje, Shweta S. (International Journal of Research in Orthopaedics, 2023)
Background: Post-operative pain is one of the most debilitating condition following lumbar spine surgery, which negates the clinical and functional outcomes. Vitamin C (ascorbic acid) due to its anti-oxidant, neuroprotective and neuromodulating properties; was evaluated to have adjuvant analgesic effects in these patients. Methods: This prospective study included 50 patients undergoing single level lumbar disectomy; randomly divided into group A (vitamin supplementation, n=25) and group B (no supplementation, n=25). Both the groups were evaluated on the follow ups for the clinical outcomes (visual analog scale-VAS score), functional outcomes (Oswestry disability index-ODI score) and total analgesia consumed. Results: Both the groups showed statistically significant improvements in clinical and functional outcomes with respect to pre-operative status. Group A showed statistically significant (p<0.05) improvement in VAS and ODI scores as compared to group B at 4th, 6th and 8th week follow up, however at 2nd and 12th week follow up the difference was found to be insignificant. Total analgesia consumed by group A patients was statistically lower than that consumed by group B patients. Conclusions: Vitamin C has analgesic effects in certain clinical conditions, thus reducing post-operative pain and improving the overall satisfaction and outcome of the surgery. It helps in bringing about the improvement in clinical as well as the functional outcome of the spine surgery and has an effective dose-sparing and adjuvant effect on the post-operative analgesia.